H3K9me3 Inhibition Improves Memory, Promotes Spine Formation, and Increases BDNF Levels in the Aged Hippocampus - Snigdha, Shikha; Prieto, G. Aleph; Petrosyan, Arpine; Loertscher, Brad M.; Dieskau, André P.; Overman, Larry E.; Cotman, Carl W. (The Journal of neuroscience, 2016)
An increasing number of studies show that an altered epigenetic landscape may cause impairments in regulation of learning and memory-related genes within the aged hippocampus, eventually resulting in cognitive deficits in the aged brain. One such epigenetic repressive mark is trimethylation of H3K9 (H3K9me3), which is typically implicated in gene silencing. Here, we identify, for the first time, an essential role for H3K9me3 and its histone methyl transferase (SUV39H1) in mediating hippocampal memory functions. Pharmacological inhibition of SUV39H1 using a novel and selective inhibitor decreased levels of H3K9me3 in the hippocampus of aged mice, and improved performance in the objection location memory and fear conditioning tasks and in a complex spatial environment learning task. The inhibition of SUV39H1 induced an increase in spine density of thin and stubby but not mushroom spines in the hippocampus of aged animals and increased surface GluR1 levels in hippocampal synaptosomes, a key index of spine plasticity. Furthermore, there were changes at BDNF exon I gene promoter, in concert with overall BDNF levels in the hippocampus of drug-treated animals compared with control animals. Together, these data demonstrate that SUV39H1 inhibition and the concomitant H3K9me3 downregulation mediate gene transcription in the hippocampus and reverse age-dependent deficits in hippocampal memory. SIGNIFICANCE STATEMENT Cognitive decline is a debilitating condition associated with not only neurodegenerative diseases but also aging in general. However, effective treatments have been slow to emerge so far. In this study, we demonstrate that epigenetic regulation of key synaptic proteins may be an underlying, yet reversible, cause of this decline. Our findings suggest that histone 3 trimethylation is a probable target for pharmacological intervention that can counteract cognitive decline in the aging brain. Finally, we provide support to the hypothesis that, by manipulating the enzyme that regulates H3K9me3 (using a newly developed specific inhibitor of SUV39H1), it is possible to alter the chromatin state of subjects and restore memory and synaptic function in the aging brain.